1999
DOI: 10.1002/j.2168-9830.1999.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Designing Engineering Courses*

Abstract: Some principles that have guided the development of engineering courses in the past are identified and applied to the development of strategies for contemporary circumstances. Implications of current changes in constraints are explored for class meetings and for student work outside of class. The realization that two‐thirds of a typical university academic course, and most of the learning, occurs outside the class meeting times compels careful focus by faculty on the design of interactive learning experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In particular, Hagler and Marcy [1] noted that if two-thirds of the time spent by students on a university course is assumed to occur outside the classroom, emphasis on reforming engineering education inside the classroom ignores the optimal target for improvement. Additionally, they suggested that this historical emphasis on the classroom experience also jeopardizes our obligation to cultivate lifelong learners who feel responsible for their own learning experience.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Hagler and Marcy [1] noted that if two-thirds of the time spent by students on a university course is assumed to occur outside the classroom, emphasis on reforming engineering education inside the classroom ignores the optimal target for improvement. Additionally, they suggested that this historical emphasis on the classroom experience also jeopardizes our obligation to cultivate lifelong learners who feel responsible for their own learning experience.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several attempts to revise engineering curricula to improve understanding and foster independent thinking. 2,3,4 Torda discussed the fate of one program developed at the Illinois Institute of Technology. 2 Our approach has many of the same goals: to promote curiosity and enthusiasm through greater student participation.…”
Section: Introductionmentioning
confidence: 99%
“…Some classes, if students are lucky, have accompanying laboratory practices where they can gain hands-on experience. There have been several attempts to revise engineering curriculum to improve understanding and foster creative thinking 3 .…”
Section: The State Of the Artmentioning
confidence: 99%